The three-dimensional molecular structure of the desmosomal plaque - Al-Amoudi, Ashraf; Devos, Damien; Russell, Robert B. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
The cytoplasmic surface of intercellular junctions is a complex network of molecular interactions that link the extracellular region of the desmosomal cadherins with the cytoskeletal intermediate filaments. Although 3D structures of the major plaque components are known, the overall architecture remains unknown. We used cryoelectron tomography of vitreous sections from human epidermis to record 3D images of desmosomes in vivo and in situ at molecular resolution. Our results show that the architecture of the cytoplasmic surface of the desmosome is a 2D interconnected quasiperiodic lattice, with a similar spatial organization to the extracellular side. Subtomogram averaging of the plaque region reveals two distinct layers of the desmosomal plaque: a low-density layer closer to the membrane and a high-density layer further away from the membrane. When combined with a heuristic, allowing simultaneous constrained fitting of the high-resolution structures of the major plaque proteins (desmoplakin, plakophilin, and plakoglobin), it reveals their mutual molecular interactions and explains their stoichiometry. The arrangement suggests that alternate plakoglobin-desmoplakin complexes create a template on which desmosomal cadherins cluster before they stabilize extracellularly by binding at their N-terminal tips. Plakophilins are added as a molecular reinforcement to fill the gap between the formed plaque complexes and the plasma membrane.
Gesehen am 16.05.2017